1938
DOI: 10.2307/1537568
|View full text |Cite
|
Sign up to set email alerts
|

The Transport of Carbon Dioxide by Erythrocytes and Plasma in Dogfish Blood

Abstract: During the summer of 1936, unsuccessful attempts were made by J. K. W. F. and J. R. P. to measure (using the chemical method of Ferguson and Roughton, 1934) the carbamino compounds of CO 2 with hemoglobin of mackerel blood and dogfish blood. The difficulty of preparing stable solutions of hemoglobin from these bloods proved to be the most serious obstacle. An attempt was then made to apply the kinetic method of Meldrum and Roughton (1933) to dogfish blood. This too was unsuccessful because carbonic anhydrase c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1940
1940
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 6 publications
(6 reference statements)
0
6
1
Order By: Relevance
“…Similarly, Ferguson, Horvath & Pappenheimer (1938) found that the addition of fluoride caused dog-fish cells to haemolyse, and later this phenomenon was observed by lamdi & Ferguson (1940) with the blood of the tautog, sea-robin and squeteague. Ferguson et at.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, Ferguson, Horvath & Pappenheimer (1938) found that the addition of fluoride caused dog-fish cells to haemolyse, and later this phenomenon was observed by lamdi & Ferguson (1940) with the blood of the tautog, sea-robin and squeteague. Ferguson et at.…”
Section: Discussionmentioning
confidence: 75%
“…Calcium and sodium transfer in tortoise erythrocytes Black & Irving (1938) found that if carp's blood were oxalated haemolysis occurred. Similarly, Ferguson, Horvath & Pappenheimer (1938) found that the addition of fluoride caused dog-fish cells to haemolyse, and later this phenomenon was observed by lamdi & Ferguson (1940) with the blood of the tautog, sea-robin and squeteague. Ferguson et at.…”
Section: Effects Of Cell Sodium Concentration ([Nat]) On the Permeabimentioning
confidence: 75%
See 1 more Smart Citation
“…It is evident that the best fit of E m calc to E m meas values as seen in Fig. 4 is where the percent volume of the cells occupied by the nucleus is 28.7% (open circles). The quantitative values at pH 7.2 as seen in Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Carbamino C 0 2 may or may not constitute a significant component, depending on the species (Ferguson et al 1938;Ferguson and Black 194 1). Heming (1984) has calculated that carbamino C02 accounts for approximately 5% of Cco2 in rainbow trout blood.…”
Section: Sco2mentioning
confidence: 99%